The community perception to acceptance of management system by zakat institutions at Kuala Kubu Bharu / Muhamad Amiruddin Tom Ali - Tom Ali, Muhamad Amiruddin (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
In this era of contemporary Islamic world, the knowledge about zakat has become a widespread concentration in which it is a common practice in Malaysia. There are many zakat institutions that have been set up in Malaysia to facilitate Muslims to deal with zakat payments and to seek help from zakat institutions. Lembaga Zakat Selangor plays an important role in ensuring that the rate of poverty of Islam in Selangor can be solved from the point of distribution of zakat to zakat recipients (Asnaf) and zakat institutions themselves identify those who are entitled to zakat. This study has been conducted to determine the perception of the community on the acceptance of management system by Zakat institutions in one of the districts of Kuala Kubu Bharu. This study was conducted based on quantitative methods such as questionnaire about the management of zakat system distributed around the Kuala Kubu Bharu area. Where are many Islamic people in the Area to make it easy to find respondents to answer the questionnaires that have been prepared and there are a some of the Muslims who lack deeper understanding of the management of the zakat system in Kuala Kubu Bharu Area. Once the data and the results of the study are collected, this data has been analyzed and the results have been systematically recorded. Based on these findings, the various perceptions of Islam regarding the acceptance of the management system by zakat institutions were known. In addition, there are discussions on the proposal in this study as a reference to the zakat system in Kuala Kubu Bharu.